2016
DOI: 10.1590/1983-21252016v29n419rc
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation With Saline Water and Nitrogen in Production Components and Yield of Sunflower

Abstract: -Due to the quantitative and qualitative limitation of water resources, saline water irrigation and nitrogen (N) fertilisation can contribute positively to the expansion of sunflower cultivation in the semiarid region of Northeast Brazil. Thus, this study aimed to evaluate production components and yield of sunflower, cv. "Embrapa 122-V2000", irrigated with waters of different salinity levels (electrical conductivity -ECw) and fertilised with varying amounts of N in a field experiment in an eutrophic Quartzare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
4
0
1
Order By: Relevance
“…The increases in the masses of one thousand achenes can be attributed to the functions of N in the metabolism of the reserve compounds in the seeds. The obtained results corroborate those of Santos et al (2016), who studied the effect of N fertilization on sunflower production using the BRS 122 cultivar and reported a mass gain of 8.45% for each 20 kg ha -1 of N applied. At the same time, Lobo, Grassi Filho and Coelho (2012) and Ahmad et al (2018) obtained nitrogen fertilization results for the H251 hybrid and reported an increase of 23.8% for doses of 50 to 300 kg ha -1 of N for the mass of 1000 achenes.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The increases in the masses of one thousand achenes can be attributed to the functions of N in the metabolism of the reserve compounds in the seeds. The obtained results corroborate those of Santos et al (2016), who studied the effect of N fertilization on sunflower production using the BRS 122 cultivar and reported a mass gain of 8.45% for each 20 kg ha -1 of N applied. At the same time, Lobo, Grassi Filho and Coelho (2012) and Ahmad et al (2018) obtained nitrogen fertilization results for the H251 hybrid and reported an increase of 23.8% for doses of 50 to 300 kg ha -1 of N for the mass of 1000 achenes.…”
Section: Resultssupporting
confidence: 88%
“…The research data recommend doses above 80 kg ha -1 of N for the most productive sunflower cultivars under semiarid irrigated conditions (Oliveira et al, 2012;Vasconcelos et al, 2015;Santos et al, 2016).…”
Section: Resultsmentioning
confidence: 94%
“…Among these, we can highlight the studies carried out with jackfruit (Artocarpus heterophyllus L. -Oliveira et al, 2017;Oliveira et al, 2018), cotton (Gossypium hirsutum L. -Chen et., 2010), sugar cane (Saccharum sp. -Nadian et al, 2012), maize (Zea mays L. -Akram et al, 2011), wheat (Triticum aestivum L. -Elgharably et al, 2010) and sunflower (Helianthus annuus L. -Santos et al, 2016). Therefore, the aim of this study was to evaluate the ecophysiological responses of Annona squamosa L. submitted to different salinity levels and nitrogen doses.…”
Section: Introductionmentioning
confidence: 99%
“…Em outra pesquisa Santos et al (2016d) avaliando os componentes de produção e rendimento do girassol, cv.…”
Section: Simões Et Al (unclassified